PENGARUH KEDISIPLINAN, KEMAMPUAN KERJA DAN DESAIN PEKERJAAN TERHADAP PRESTASI KERJA KARYAWAN PT TELKOM AKSES PUGERAN YOGYAKARTA - Dyan Elsiningtyas; Audita Nuvriasari (MANAJEMEN DEWANTARA, 2023)
The objective of this study is to analyze the influence of discipline, work ability and job design on the work performance of PT Telkom Access Pugeran Yogyakarta. This type of research is quantitative research using descriptive and inferential statistical tools. The sampling technique uses quota sampling with a total sample of 55 employees. The results of this study indicate that work ability has a positive and significant effect on employees of PT Telkom Akses Pugeran Yogyakarta while discipline and job design do not have a significant effect on the work performance.